Thymidine uptake, thymidine incorporation, and thymidine kinase activity in marine bacterium isolates. - Jeffrey, W H (1990)
One assumption made in bacterial production estimates from [3H]thymidine incorporation is that all heterotrophic bacteria can incorporate exogenous thymidine into DNA. Heterotrophic marine bacterium isolates from Tampa Bay, Fla., Chesapeake Bay, Md., and a coral surface microlayer were examined for thymidine uptake (transport), thymidine incorporation, the presence of thymidine kinase genes, and thymidine kinase enzyme activity. Of the 41 isolates tested, 37 were capable of thymidine incorporation into DNA. The four organisms that could not incorporate thymidine also transported thymidine poorly and lacked thymidine kinase activity. Attempts to detect thymidine kinase genes in the marine isolates by molecular probing with gene probes made from Escherichia coli and herpes simplex virus thymidine kinase genes proved unsuccessful. To determine if the inability to incorporate thymidine was due to the lack of thymidine kinase, one organism, Vibrio sp. strain D19, was transformed with a plasmid (pGQ3) that contained an E. coli thymidine kinase gene. Although enzyme assays indicated high levels of thymidine kinase activity in transformants, these cells still failed to incorporate exogenous thymidine into DNA or to transport thymidine into the cells. These results indicate that the inability of certain marine bacteria to incorporate thymidine may not be solely due to the lack of thymidine kinase activity but may also be due to the absence of thymidine transport systems.